Contextual Causes of Implicature Failure. Issue 3 (3rd April 2017) - Cummins, Chris
Abstract : Theoretical and empirical research on quantity implicature has concurred that pragmatically strengthened, richer readings are not available when they are not relevant to the discourse purpose. However, this claim relies on an appeal to a notion of "relevance" that has proved difficult to make precise. In this article I discuss and contrast two potential contributory factors to relevance: adherence to the Question Under Discussion, and form-based priming effects. The former can be considered to operate at a relatively high level of analysis, from the speaker's perspective, and influences the semantic content that the speaker should be attempting to convey, whereas the latter is assumed to reflect low-level psychological preferences and influences the form of words that the speaker should use. I argue that pragmatics, and specifically implicature, constitutes a useful testbed for distinguishing these effects—the availability of an implicature can be used as an indicator that a particular stronger alternative would also have been an acceptable utterance, whereas its unavailability suggests that the stronger alternative would not necessarily have been acceptable. I discuss recent experimental data from this perspective and argue that both Question Under Discussion and priming effects are customarily at play. I conclude by exploring the implications of this for our view of pragmatics and its interfaces.